Analisis kebutuhan media pembelajaran matematika materi dimensi-tiga berbasis teknologi augmented reality - Muhammad Farhan Pranata; Hepsi Nindiasari; Sukirwan Sukirwan (Universitas Sultan Ageng Tirtayasa, 2023)
Learning media are currently using technology in their development. One of the uses of technology in learning media is the use of augmented reality. Augmented reality functions is a technology that realizes an object via a smartphone. Before developing an application, it is necessary to have a needs analysis that can help the process of developing the learning media. The use of augmented reality is to make the students more interesting to the teacher explanation in learning activity. This study aims to analyze what needs are needed to develop augmented reality-based learning media applications. Needs analysis aims to see what needs are to develop applications in terms of hardware and software. In addition, there needs to be an application design that is easy to use by anyone, both teachers and students. The research method is to collect literature study, make observations during learning, and interview teachers and students to see what things are needed in the application. The final result of this research is an augmented reality application design in three-dimensional material.